Lipid nanoparticle composition for adjuvant formulation modulates disease after influenza virus infection in quadrivalent influenza vaccine vaccinated mice - Jangra, Sonia; Lamoot, Alexander; Singh, Gagandeep; Laghlali, Gabriel; Chen, Yong; Ye, Tingting; García-Sastre, Adolfo; De Geest, Bruno G.; Schotsaert, Michael (Frontiers in Immunology, 2024)
There are considerable avenues through which currently licensed influenza vaccines could be optimized. We tested influenza vaccination in a mouse model with two adjuvants: Sendai virus-derived defective interfering (SDI) RNA, a RIG-I agonist; and an amphiphilic imidazoquinoline (IMDQ-PEG-Chol), a TLR7/8 agonist. The negatively charged SDI RNA was formulated into lipid nanoparticles (LNPs) facilitating direct delivery of SDI RNA to the cytosol, where RIG-I sensing induces inflammatory and type I interferon responses. We previously tested SDI RNA and IMDQ-PEG-Chol as standalone and combination adjuvants for influenza and SARS-CoV-2 vaccines. Here, we tested two different ionizable lipids, K-Ac7-Dsa and S-Ac7-Dog, for LNP formulations. The LNPs were incorporated with SDI RNA to determine its potential as a combination adjuvant with IMDQ-PEG-Chol by evaluating the host immune response to vaccination and infection in immunized BALB/c mice. Adjuvanticity of IMDQ-PEG-Chol with and without empty or SDI-loaded LNPs was validated with quadrivalent inactivated influenza vaccine (QIV), showing robust induction of antibody titers and T-cell responses. Depending on the adjuvant combination and LNP formulation, humoral and cellular vaccine responses could be tailored towards type 1 or type 2 host responses with specific cytokine profiles that correlated with the protective responses to viral infection. The extent of protection conferred by different vaccine/LNP/adjuvant combinations was tested by challenging mice with a vaccine-matched strain of influenza A virus A/Singapore/gp1908/2015 IVR-180 (H1N1). Groups that received either LNP formulated with SDI or IMDQ-PEG-Chol, or both, showed very low levels of viral replication in their lungs at 5 days post-infection (DPI). These studies provide evidence that the combination of vaccines with LNPs and/or adjuvants promote antigen-specific cellular responses that can contribute to protection upon infection. Interestingly, we observed differences in humoral and cellular responses to vaccination between different groups receiving K-Ac7-Dsa or S-Ac7-Dog lipids in LNP formulations. The differences were also reflected in inflammatory responses in lungs of vaccinated animals to infection, depending on LNP formulations. Therefore, this study suggests that the composition of the LNPs, particularly the ionizable lipid, plays an important role in inducing inflammatory responses in vivo, which is important for vaccine safety and to prevent adverse effects upon viral exposure.